Produção e caracterização bioquímica de lipases produzidas por fungos filamentosos - Zavarise, Julio Pansiere (2021)
The cost of production and purification of lipases is considered as an obstacle to their ostentatious application in industrial processes. Alternatively, purified lipases can be used lipases bounded to mycelium (intracellular lipases) and broth fermented with extracellular lipases, both produced by filamentous fungi. In this context, there is an apparent research gap on the simultaneous production of such multiple forms of lipases by filamentous fungi. Therefore, the aim of this study is to investigate the production potential of intracellular and extracellular lipases from three fungal strains (Aspergillus niger, Penicillium sp. F02 and Trichoderma koningii) and perform biochemical characterization of the lipases produced. The submerged cultivation of filamentous fungi was carried out in Erlenmeyers, with olive oil as a carbon source. The activities (intracellular and extracellular) were determined by the hydrolysis method of olive oil. The effect of substrate concentration, pH and temperature on lipasic activities were evaluated. The results obtained indicate that T. koningii presented the maximum intracellular lipasic activity (81.5 IU/g of dry biomass), while for extracellular lipasic activity (10.6 IU/ml of fermented broth) this was found for A. niger. The analysis of specific activities (ratio between lipase activity and dry biomass concentration) indicated that Trichoderma presented a differentiated behavior, with indications that there is a strong retention of lipases in mycelium. The values of the kinetic parameters determined for the lipases produced, with the emulsion of commercial olive oil as substrate, ranged from 68.24 to 469.04mM for Km and from 5.58 to 37.88 IU for Vmax. Statistical analysis indicated that the effect of pH on intracellular lipasic activity of T. koningii was about 13 times greater than the effect of temperature. The reaction allocated temperatures in the range of 37°C to 44°C and the pH from 7.8 to 8.0 favored the activities of lipases produced by T. koningii.